Coronary CT angiography with prospective ECG-triggering: An effective alternative to invasive coronary angiography - Sun, Zhonghua (AME Publishing Company, 2012)
Despite the tremendous contributions of coronary CT angiography to coronary artery disease, radiation dose associated with coronary CT angiography has raised serious concerns in the literature, as the risk of developing radiation-induced malignancy is not negligible. Various dose-saving strategies have been implemented, with some of the strategies resulting in significant dose reduction. Of these strategies, prospective ECG-triggering is one of the most effective techniques with resultant effective radiation dose similar to or even lower than that of invasive coronary angiography. Prospective ECG-triggered coronary CT angiography has been reported to have high diagnostic accuracy in the diagnosis of coronary artery disease with image quality comparable to that of retrospective ECG-gating, but with significantly reduced radiation dose. Successful performance of prospective ECG-triggering is determined by strict exclusion criteria and careful patient preparation. The aim of this article is to provide an overview of the diagnostic applications of coronary CT angiography with prospective ECG-triggering with focus on radiation dose reduction. Radiation dose measurements are discussed with aim of allowing accurate dose estimation. Diagnostic value of prospective ECG-triggered coronary CT angiography in patients with different heart rate is discussed. Finally, current status and future directions are highlighted.